TKI RELATED CARDIOTOXICITY IN METASTATIC SOLID ORGAN TUMORS PRESENTING IN ONCOLOGY DEPARTMENT CMH RAWALPINDI (The Research of Medical Science Review, 2025)
Background: Although their use is linked with great cardiotoxicity, which can affect survival results, tyrosine kinase inhibitors (TKIs) are extensively employed in the therapy of metastatic solid organ cancers. Objectives: The frequency, risk factors, and effects of TKI-related cardiotoxicity in patients treated at the Oncology Department, CMH Rawalpindi were examined in this work. Methods: 180 patients with metastatic solid organ cancers undergoing TKI treatment from April 2024 to November 2024 were included in this cross-sectional analysis. Clinical, biochemical and echocardiographic data were used to evaluate cardiotoxicity. Using multivariate logistic regression, risk factors were examined; survival results were then assessed.Results: Cardiotoxicity was reported in 41.7% of individuals; the most often occurring problems were left ventricular dysfunction (17.2%) and hypertension (25%). Age >60 years (OR: 3.46, p<0.001), smoking (OR: 1.93, p=0.019), history of hypertension (OR: 2.54, p=0.004) and TKI therapy duration >8 months (OR: 4.17, p<0.001) were among the risk variables most definitely linked to cardiotoxicity. In cardiotoxic group, echocardiographic results showed lower left ventricular ejection fraction (50.4% vs. 62.7%), and higher pulmonary artery pressures. p = 0.001, strongly linked with cardiotoxicity (p<0.001 were elevated biomarker values including troponin-I and NT-proBNP). Patients with cardiotoxicity had notably reduced total survival (12.3 vs. 16.2 months, p = 0.001) and progression-free survival (8.7 vs. 12.5 months, p = 0.001). Conclusion: Cardiotoxicity is a prevalent and clinically important side effect of TKI treatment that compromises cardiovascular health and survival results. Early interventions, biomarker evaluations, and regular cardiovascular monitoring help to reduce these risks and maximize therapy results for patients on TKI medication.